Assessment of curve of spee in different malocclusions - Hüsamettin Oktay; Gülşilay Sayar (Istanbul University, 2018)
DOI: 10.26650/eor.2018.475Purpose The aim of this study was to compare the depth of curve of Spee (COS) in Angle Class I, Angle Class II and Angle Class III malocclusions. Materials and methods The Samples were chosen among the diagnostic materials in İstanbul Medipol University Department of Orthodontics. Ninety plaster models were chosen, and were divided into 3 groups (n=30) according to Angle dental malocclusion classification. The depth of curve of Spee was measured on left and right sides of mandibular dental models and mean values were used as depth of curve of Spee. ANOVA test was used to evaluate normally distributed data. Comparison of the sides were performed by using paired sample t test. Significance level was set to p<0.05. Results The depth of COS was found as deepest in Class II malocclusion (2.9±0.8 mm) and was relative flat in Class III malocclusion (2.1±0.9 mm) and the difference was statistically significant (p<0.05). No significant difference was found between Angle Class I and Class III malocclusions. Conclusion Since the depth of curve of Spee is increased in Class II malocclusions, this factor should be considered in treatment planning.